The importance of redefining power for understanding women's engagement in healthcare in Uganda - Singh, D.; Lample, M.; Earnest, Jaya (Curtin University, 2012)
Conceptions of power in contemporary discourse surround the most tangible forms of power: physical, political, social and economic. Competition and self-interest also tend to be at the centre of discussions around power. Even within the family, power is looked at within the framework of domination and the capacity to pursue one's own self-interest. When power is viewed through the lens of coercion, competition and self-interest, one is looking at forms of power that have traditionally benefitted men and often oppressed women. For the purpose of this cross-sectional, exploratory study, we decided to view power as the ‘ability’ and ‘capacity’ an individual possesses. By broadly looking at power as a capacity, forms of power within a family and community structure become clearer. Multiple methods using focus group discussions, informant interviews, observations and a descriptive questionnaire were used to explore the views of Ugandan men and women on healthcare decisions. The analysis revealed that while women are gaining decision-making power in a number of areas, health decisions appear unique as a space where the knowledge of women was highly valued. We therefore suggest power be redefined and women take a lead role uplifting the community through engagement in healthcare decision-making and delivery.